Synthesis, structure, and optical properties of an alternating calix[4]arene-based meta-linked phenylene ethynylene copolymer - D. Barata, Patrícia (2011)
Novel alternating copolymers comprising biscalix[4]arene-p-phenylene ethynylene and m-phenylene ethynylene units (CALIX-m-PPE) were synthesized using the Sonogashira-Hagihara cross-coupling polymerization. Good isolated yields (60-80%) were achieved for the polymers that show M-n ranging from 1.4 x 10(4) to 5.1 x 10(4) gmol(-1) (gel permeation chromatography analysis), depending on specific polymerization conditions. The structural analysis of CALIX-m-PPE was performed by H-1, C-13, C-13-H-1 heteronuclear single quantum correlation (HSQC), C-13-H-1 heteronuclear multiple bond correlation (HMBC), correlation spectroscopy (COSY), and nuclear overhauser effect spectroscopy (NOESY) in addition to Fourier transform-Infrared spectroscopy and microanalysis allowing its full characterization. Depending on the reaction setup, variable amounts (16-45%) of diyne units were found in polymers although their photophysical properties are essentially the same. It is demonstrated that CALIX-m-PPE does not form ground-or excited-state interchain interactions owing to the highly crowded environment of the main-chain imparted by both calix[4]arene side units which behave as insulators inhibiting main-chain pi-pi staking. It was also found that the luminescent properties of CALIX-m-PPE are markedly different from those of an all-p-linked phenylene ethynylene copolymer (CALIX-p-PPE) previously reported. The unexpected appearance of a low-energy emission band at 426 nm, in addition to the locally excited-state emission (365 nm), together with a quite low fluorescence quantum yield (Phi = 0.02) and a double-exponential decay dynamics led to the formulation of an intramolecular exciplex as the new emissive species.